Misunderstandings (and some criticisms) in social network analysis - Borgatti, Steve (AWARI, 2023)
The Chilean Society for Social Network Science (ChiSocNet) has played a pivotal role in the organization of the social networking community in South America, Ibero-America, and beyond in recent years. It recently spearheaded the inaugural Chilean Social Networking Conference (ChiSocNet), held in Santiago, Chile, from January 4-7, 2023. This conference brought together researchers and practitioners from diverse backgrounds, united by a shared interest in the social networking perspective. The program consisted of 13 sessions on nine topics, with more than 80 presentations. In addition, 180 individuals registered to attend the conference, including speakers and the general public. Furthermore, six free workshops were held, with registrations ranging from 40 to 100 people, depending on the topic. In this context, the international keynote address was delivered by Steve Borgatti, Professor and Chair of the Department of Management in the College of Business at the University of Kentucky. A transcript of this presentation is provided in this article.